Design of Embedded System for Grid Handtop Computing(ESGHC) - Lim Kek, Yong; Wong Poh, lee; Chan Huah, Yong; Mohd Azam, Osman (2008)
ESGHC applies the grid computing technology which is built under a grid environmentfor handtop devices. By having ESGHC, sharing of handtop devices in terms of computational power and storage are virtually possible.